A comparison between Vanadyl, Vanadate, and decavanadate effects in actin structure and function: combination of several spectroscopic studies - Aureliano, M. (2012)
The studies about the interaction of actin with vanadium are seldom. In the present paper the effects of vanadyl, vanadate, and decavanadate in the actin structure and function were compared. Decavanadate clearly interacts with actin, as shown by 51V-NMR spectroscopy. Decavanadate interaction with actin induces protein cysteine oxidation and vanadyl formation, being both prevented by the natural ligand of the protein, ATP. Monomeric actin (G-actin) titration with vanadyl, as analysed by EPR spectroscopy, indicates a 1 : 1 binding stoichiometry and a kd of 7.5 μM. Both decavanadate and vanadyl inhibited G-actin polymerization into actin filaments (F-actin), with a IC50 of 68 and 300 μM, respectively, as analysed by light-scattering assays. However, only vanadyl induces G-actin intrinsic fluorescence quenching, which suggests the presence of vanadyl high-affinity actin-binding sites. Decavanadate increases (2.6-fold) actin hydrophobic surface, evaluated using the ANSA probe, whereas vanadyl decreases it (15%). Finally, both vanadium species increased ε-ATP exchange rate (k = 6.5 × 10−3 and 4.47 × 10−3 s−1 for decavanadate and vanadyl, resp.). Putting it all together, it is suggested that actin, which is involved in many cellular processes, might be a potential target not only for decavanadate but above all for vanadyl.